Performance evaluation of water supply services in Chitungwiza: How water supply services mirrors poor governance and lack of management - Luckson Zvobgo (Journal of Local Government Research and Innovation, 2020)
Background: Provision of reliable water services is crucial for urban livelihood. In Chitungwiza, provision of water services has been deteriorating since the millennium with residents losing hope for better services. The poor supply of municipal water in Chitungwiza has led to a chronic ‘dry taps situation’ where household taps are dry from periods of several consecutive days to months.